The use of mobile learning application in interview role-play: A preliminary study - Lam, Catherine Nguoi Chui (Institute of Advanced Scientific Research, Inc., 2020)
This paper gives an overview of a preliminary study which aims to shed light on one of the most popular communicative activities in English as a Second Language (ESL) classroom, i.e interview role-play conducted with a video response application-Flipgrid, a platform which allows easy video submissions and responses from the students. An intact class of thirteen (13) Diploma in Mechanical Engineering students taking Communicative English 3 in one of the polytechnic institutions in Malaysia has participated in this study. Participants’ spoken data and perceived usefulness and enjoyment of using the mobile learning application were explored. Interview role-play based on the use of the mobile learning application was carried out to prepare students for Mock Job Interview assessment. Findings revealed that incorrect choice of tense, omission of plural forms and omission of verb forms are the three main language problems faced by the learners. Apart from learners’ positive perceptions towards the use of the mobile learning application in their interview role-play, the overall findings also showlearners’ favourable responses correspond to their perceived enjoyment of using the application. The findings thus highlight the potential use of mobile learning application, specifically the use of video recording in interview role-play.